The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1091/mbc.e16-08-0618
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-induced distinct epialleles are phosphorylated at either H3S10 or H3S28, depending on H3K27 acetylation

Abstract: Upon mitogenic induction of immediate-early genes, phosphorylation of histone H3 at S10 or S28 occurs on different alleles. S28ph depends on CBP/p300-mediated K27ac, whereas H3 acetylated on K9 by PCAF is phosphorylated on S10. The redundant roles of S10ph and S28ph and their random targeting on distinct alleles may enable a fast response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
0
14
1
Order By: Relevance
“…Interphase phospho-H3S10 mark is deposited on actively transcribed genes by multiple kinases ( [64,97], formaldehyde [98], cigarette smoke [99], ionizing radiation [53], H3S10ph may represent a mechanistic link between carcinogens and cellular transformation. This hypothesis is supported by the studies indicating that TPA or epidermal growth factor (EGF)-induced MSK1 activity and H3S10ph is required for transformation of mouse epidermal cells [16,100].…”
Section: Interphase Kinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interphase phospho-H3S10 mark is deposited on actively transcribed genes by multiple kinases ( [64,97], formaldehyde [98], cigarette smoke [99], ionizing radiation [53], H3S10ph may represent a mechanistic link between carcinogens and cellular transformation. This hypothesis is supported by the studies indicating that TPA or epidermal growth factor (EGF)-induced MSK1 activity and H3S10ph is required for transformation of mouse epidermal cells [16,100].…”
Section: Interphase Kinasesmentioning
confidence: 99%
“…Multiple IEGs encode transcription factors, such as c-MYC, c-FOS, c-JUN, FOS1L, EGR1 , that are responsible for transcriptional reprogramming of cells exposed to environmental stress-inducing stimuli. Since many of these IEGs are oncogenes, and H3S10 phosphorylation is typically triggered by factors known to be potentially carcinogenic, such as exposure to 12-O-tetradecanoylphorbol-13-acetate (TPA) [ 64 , 97 ], formaldehyde [ 98 ], cigarette smoke [ 99 ], ionizing radiation [ 53 ], H3S10ph may represent a mechanistic link between carcinogens and cellular transformation. This hypothesis is supported by the studies indicating that TPA or epidermal growth factor (EGF)-induced MSK1 activity and H3S10ph is required for transformation of mouse epidermal cells [ 16 , 100 ].…”
Section: Interphase Kinasesmentioning
confidence: 99%
“… 38 H3K27 acetylation and S28 phosphorylation are directly coupled, and such combination can functionally antagonize PRC2-mediated H3K27me3 mark. 39 Using a NIR inducible knockdown cell line, we found that silencing of NIR resulted in increased H3K27ac and reduction of H3K27me3 level at the promoter region of FOXO3, implying the intricated balance of H3K27ac and H3K27me3 levels by NIR through modulating PRC2 activity. Since NIR has INHAT (inhibitor of histone acetyltransferase) activity, the interaction of NIR and EZH2 may block the accessibility of acetyltransferases to catalyze H3K27ac, while facilitating PRC2 to catalyze the H3K27me3 mark.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, a study investigating such a histone modification in OSCC showed its relationship with tumorigenesis and poor outcomes . Also, H3S10ph may be directly involved in tumorigenesis by inducing the transcription of some developmental genes, including Hox and immediate‐early genes . In another study, the MYC proto‐oncogene protein product was shown to be able to activate cancer‐promoting genes by recruiting the H3S10ph kinase PIM‐1 .…”
Section: Discussionmentioning
confidence: 94%